EXTENDED ESSAY ON ORIENTALISM IN THE PAINTED VEIL BY WILLIAM SOMERSET MAUGHAM - Hasani, Mj Rizqon (LANTERN (Journal on English Language, Culture and Literature), 2016)
In this paper, the writer discuss orientalism in William Somerset Maugham’s The painted Veil. The purpose of the paper is to analyze how West describes the East and how the East looks at the West. The conflicts, the settings, and the characters in the novel are also shown in order to supporting the orientalism. It also discusses how the orientalism works in this novel and how the relation between the occident or the west and the orient or the east. In doing this research, the writer uses method of library research. The object of the paper is William Somerset Maugham’s The painted Veil. The writer also uses postcolonial approach to help explain the issues in The Painted Veil. To investigate the issues, the writer uses orientalism theory by Edward Said.From the discussion in the paper the writer finds that there are some parts that show the British view towards Chinese. The orientalism in this novel is also shown in some parts such as the policy of British in China, the purpose of conquering China, and in comparison of The West religion and The East Religion.